Antropologia da inclusão religiosa judaica - conversão ao judaísmo online: a incorporação dos rituais religiosos judaicos em ambiências virtuais - Lima, Alan Freire de (2024)
This book, the result of a doctoral thesis in anthropology, investigates the incorporation of virtual environments into Jewish culture, including websites, digital platforms and virtual learning environments. The work focuses particularly in the study and conversion programs to Judaism offered 100% online, in addition to mentioning other Jewish websites. Describe and discuss three specific websites for rabbi-mediated conversion to Judaism: Make me Jewish (Convert to Judaism online) by non-Orthodox rabbi Marc Rubenstein, Converting to Judaism by Orthodox Rabbi Gedalia Walls, and Darshan Yeshiva, a rabbinate made up of dozens of rabbis from diverse backgrounds non-Orthodox Jewish denominations. The research is divided into three main axes: 1. Conceptions of digital technologies, cyberspace, cyberculture and cyber-religion. 2. Anthropological theory on cultural genesis, conceptions of culture, Jewish identity and the relationship between Judaism and its ancestry and modernity. 3. Theories on Jewish religious exclusion and inclusion and human plurality. The importance of this research lies in its ability to shed light on the how digital technologies are transforming religious practices traditional. By exploring the offer of conversion to Judaism through online platforms, the study reveals a contemporary phenomenon of religious democratization, where geographic and social barriers are overcome, allowing individuals from different parts of the world to access and participate of rituals and conversion processes previously restricted to contexts face-to-face. Furthermore, the research highlights the relevance of the subject when addressing issues of cultural and religious identity in an increasingly digital world. O Judaism, with its long history and rich traditions, finds itself on the platforms digital a new space of expression and continuity, reflecting both the preservation and adaptation of their practices. Analysis of the differences between orthodox and unorthodox approaches in the use of these technologies highlights the internal diversity of Judaism and the plurality of paths to experience religious. The study also has significant implications for understanding the religious pluralism and inclusion. When discussing how digital platforms can both include and exclude individuals, the research offers a reflection critical review of the challenges and opportunities of cyberspace for religious practice. Overcoming Jewish religious fundamentalism and prejudices, promoted by these new forms of interaction, is a crucial aspect of the debate contemporary about religion and technology. Thus, this book not only documents an emerging phenomenon, but also contributes to the broader dialogue about the role of technology in transformation of religious and cultural practices. By offering an analysis detailed and in-depth websites for conversion to Judaism and its mediation by rabbis, the work becomes essential reading for religious scholars, anthropology, sociology and technology, as well as for anyone interested in the intersection between tradition and modernity in the digital world.